A simplified composite outcome measure to assess the effect of periodontal regenerative treatment in intraosseous defects. Issue 6 (12th January 2020) - Trombelli, Leonardo; Farina, Roberto; Vecchiatini, Renata; Maietti, Elisa; Simonelli, Anna
Abstract: Background: To propose a novel composite outcome measure (COM) for periodontal regenerative treatment of intraosseous defects. Methods: COM is based on the combination of clinically relevant clinical attachment level (CAL) gain (≥3 mm) and pocket closure (post‐surgery probing depth [PD] ≤ 4 mm). Treatment was regarded as successful when a clinically relevant CAL gain was associated with pocket closure, and failing when either clinically relevant CAL gain and pocket closure were not achieved. The effect of the different regenerative treatments was both collectively and separately evaluated according to COM in a defect cohort accessed by Single Flap Approach (SFA). Results: In the entire study cohort, the procedure resulted in a 6‐month CAL gain of 3.7 ± 1.9 mm, which was clinically relevant in 71.8% of patients. Six‐month residual PD was 3.7 ± 1.1 mm, with pocket closure recorded in 79.6% of patients. COM revealed a successful treatment in 60 patients (58%), and a treatment failure in 7 patients (7%). Mean CAL gain was clinically relevant for each treatment, whereas the residual PD values were consistent with pocket closure for the majority of treatment options. However, when COM was used to rate the treatment outcome of each procedure, it appeared that a successful treatment ranged from 41.5% to 77.5%, whereas treatment failure varied from 3% to 15% for different treatments. Conclusions: Compared to single probing measurements, COM seems (1) more accurate in capturing the overall benefit of the regenerative procedure and (2) to better identify which factor (CAL gain, residual pocket) mainly contributed to determine a treatment failure.